PERBANDINGAN MOTIVASI BELAJAR SEBELUM DAN SESUDAH PADA ANAK USIA 4-5 TAHUN - Kurniawati, Vivi; Yuniarni, Desni; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research purpose to look at prestest and posttest from comparison of learning motivation before and after using three-dimensional media. In children aged 4-5 years in kindergarten Al-Adabiy Pontianak,experimental method, using research designs.pre-experimental designs are used to conduct pre liminary studies before and after the experiment( prestest posttest) with single class. The techniques and data collection tools used are observation techniques and the tools used are observation documentation guldelires, data collected in the form of observation sheets showed research results, (1).children showattetion when the teacher conveys learning 7% for the low prestest category while 100% for the posttest were in the high category. (2).children are very excited when learning takes place 10% for low level of prestest in the category while 100/5 for the posttest were in the high category. (3).children are able to be responsible for any task given by the teacher 4% for low lever prestest in the category of entry while 34% forthe posttest for the medium category. (4).children?s reaction to things that are happening when learning takes place 0% for prestest in high category while 100% for posttest in high category. So itcanbe concluded that by using three-dimensional media, namely mini mountain eruption media is very inflvential for children because by using these media children are more enthy siastic and excited than just using the media of images and lectures only.Keywords: Theree-dimensional Media, Learning-motivasion of early Childhood Childre